Mobile App Strategy to Facilitate Human Papillomavirus Vaccination Among Young Men Who Have Sex With Men: Pilot Intervention Study - Fontenot, Holly B; White, Bradley Patrick; Rosenberger, Joshua G; Lacasse, Hailee; Rutirasiri, Chokdee; Mayer, Kenneth H; Zimet, Gregory (JMIR Publications, 2020)
BackgroundMobile app-based interventions have been identified as potential facilitators for vaccination among young men who have sex with men (MSM). ObjectiveThis pilot study aimed to test the feasibility of a theoretically informed mobile health (mHealth) tool designed to reduce health disparities and facilitate human papillomavirus (HPV) vaccination among a sample of young MSM. MethodsThe development of the mHealth tool was guided by previous research, implementation intention theory, and design thinking. We recruited MSM aged 18-26 years through a popular online dating app and linked participants to our mHealth tool, which provided HPV vaccine information and fostered access to care. ResultsA total of 42 young MSM participated in this pilot study in Boston, Massachusetts. Participants reported variable HPV knowledge (ie, high knowledge of HPV risk factors and low knowledge of HPV-related cancer risks for men) and positive vaccine beliefs and attitudes. Of those who were either unvaccinated, not up to date, or did not report vaccine status, 23% (8/35) utilized the mHealth tool to obtain HPV vaccination. Participants primarily utilized the tool's (1) educational components and (2) capabilities facilitating concrete vaccine action plans. ConclusionsWe recruited an underserved at-risk population of youth via an online dating app for our mHealth intervention that resulted in in-person health care delivery. This study was limited by enrollment challenges, including low willingness to download the mHealth tool to mobile devices.